Attracting and utilizing ethnic minority cadres and civil servants at the communal level - Nguyen Van Minh (Journal of State Management, 2025)
Vietnam is a multi-nationality and unified country with 54 ethnic groups, among which the Kinh people has the largest population. In comparison, the remaining 53 ethnic minority groups account for over 16% of the national population. Therefore, the Party and the State of Vietnam have always paid attention to issuing and implementing policies regarding ethnic minorities, prioritizing the appointment of ethnic minority cadres and civil servants. Ethnic minority cadres and civil servants have directly contributed to the socio-economic development of their localities and the country. To achieve this, attracting and utilizing ethnic minority cadres and civil servants at the communal level is considered a crucial step in ethnic minority personnel work, aiming to supplement and enhance the quantity and quality of this workforce in state agencies. However, in practice, the attraction and utilization of ethnic minority cadres and civil servants remain ineffective, mainly due to the lack of specific policies to attract and utilize ethnic minority cadres at the communal level. It is the responsibility of the Party, the State, and relevant authorities to introduce appropriate solutions and policies to address this issue. These policies should aim to attract and utilize ethnic minorities in the political system and grassroots government, ensuring their commitment to work and willingness to contribute their efforts, intelligence, and talents to local socio-economic development in the new era.